Recommendations for the referral of patients for proton-beam therapy, an Alberta Health Services report: a model for Canada? - Patel, S. (Multimed Inc., 2014)
BACKGROUND: Compared with photon therapy, proton-beam therapy (pbt) offers compelling advantages in physical dose distribution. Worldwide, gantry-based proton facilities are increasing in number, but no such facilities exist in Canada. To access pbt, Canadian patients must travel abroad for treatment at high cost. In the face of limited access, this report seeks to provide recommendations for the selection of patients most likely to benefit from pbt and suggests an out-of-country referral process. METHODS: The medline, embase, PubMed, and Cochrane databases were systematically searched for studies published between January 1990 and May 2014 that evaluated clinical outcomes after pbt. A draft report developed through a review of evidence was externally reviewed and then approved by the Alberta Health Services Cancer Care Proton Therapy Guidelines steering committee. RESULTS: Proton therapy is often used to treat tumours close to radiosensitive tissues and to treat children at risk of developing significant late effects of radiation therapy (rt). In uncontrolled and retrospective studies, local control rates with pbt appear similar to, or in some cases higher than, photon rt. Randomized trials comparing equivalent doses of pbt and photon rt are not available. SUMMARY: Referral for pbt is recommended for patients who are being treated with curative intent and with an expectation for long-term survival, and who are able and willing to travel abroad to a proton facility. Commonly accepted indications for referral include chordoma and chondrosarcoma, intraocular melanoma, and solid tumours in children and adolescents who have the greatest risk for long-term sequelae. Current data do not provide sufficient evidence to recommend routine referral of patients with most head-and-neck, breast, lung, gastrointestinal tract, and pelvic cancers, including prostate cancer. It is recommended that all referrals be considered by a multidisciplinary team to select appropriate cases.